High intensity interior aircraft noise increases the risk of high diastolic blood pressure in Indonesian Air Force pilots (Faculty of Medicine Universitas Indonesia, 2009)
Aim To analyze the effects of aircraft noise, resting pulse rate, and other factors on the risk of high diastolic blood pressure (DBP) in Indonesian Air Force pilots. Methods A nested case-control study was conducted using data extracted from annual medical check-ups indoctrination aerophysiologic training records at the Saryanto Aviation and Aerospace Health Institute (LAKESPRA) in Jakarta from January 2003 â September 2008. For analysis of DBP: the case group with DBP â¥ 90 mmHg were compared with contral group with DBP < 79 mmHG. One case matched to 12 controls. Results Out of 567 pilots, 544 (95.9%) had complete medical records. For this analysis there were 40 cases of high DBP and 480 controls for DBP. Pilots exposed to aircraft noise 90-95 dB rather than 70-80 dB had a 2.7-fold increase for high DBP [adjusted odds ratio (ORa) = 2.70; 95% confidence interval (CI ) = 1.05-6.97]. Pilots with resting pulse rates of ≥ 81/minute rather than ≤ 80/minute had a 2.7-fold increase for high DBP (ORa = 2.66; 95% CI = 1.26-5.61). In terms of total flight hours, pilots who had 1401-11125 hours rather than 147-1400 hours had a 3.2-fold increase for high DBP (ORa = 3.18; 95% CI = 1.01-10.03). Conclusion High interior aircraft noise, high total flight hours, and high resting pulse rate, increased risk for high DBP. Self assessment of resting pulse rate can be used to control the risk of high DBP. (Med J Indones 2009; 276: 276-82)